PENGGUNAAN TEOREMA PI BUCKINGHAM PADA PENYELIDIKAN LOST HEAD UNTUK PIPA MENDATAR DENGAN ALIRAN TAK KOMPRESIBEL TURBULEN - Cahyani, Indah Eko; Wibowo, Agus (Universitas Pancasakti Tegal, 2011)
Lost head can be interpreted as a decrease in the pressuregradient and is a measure of resistance to flow through the pipe. Barriers to flow through the pipeline will greatly affect the power needed in moving the fluid so that the investigation of the losthead on pipe important thing to do. Use of Buckingham Pitheorem for dimensional analysis will make it easier to analyzeand make the move quicker and directed experiments. With theinitial data is a function of the barrier pipe diameter, fluidviscosity, fluid density, pipe length, the fluid velocity and theroughness of the pipe. The results indicate a lost connection headper weight of the fluid (w p /) is proportional to the piperoughness factor (f) is proportional to the length of pipe per pipe diameter (L / d) is proportional to the fluid velocity kuwadrat pertwo times gravity (v2/2g)Keywords: Lost head, turbulent flow, the flow channel is closed